Securisation special purpose entities, bank sponsors and derivatives - Paweł Fiedor; Neill Killeen (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2019)
This paper documents the use of derivatives by securitisation special purpose entities (SPEs), also known as financial vehicle corporations (FVCs), domiciled in Ireland using transaction-level data established by the European Market Infrastructure Regulation. We show that these entities primarily engaged in interest rate derivatives over the period of 2015-2017. We find that larger entities that already engage in international capital markets are more likely to have derivative exposures. We also show that entities sponsored by banks and non-bank financial institutions are relatively more likely to engage in derivative markets. The characteristics of these bank sponsors are important in determining SPEs' engagement in derivative markets. SPEs' heavy reliance on debt finance coupled with their strong interconnectedness with bank sponsors underscores the importance of continuous monitoring and macroprudential surveillance of their derivative activities.
Keywords: F30; F36; G15; G23; 330; derivatives; shadow banking; FVCs; SPEs; EMIR; market-based finance